If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(12h + -5h) = 42 Combine like terms: 12h + -5h = 7h 6(7h) = 42 Remove parenthesis around (7h) 6 * 7h = 42 Multiply 6 * 7 42h = 42 Solving 42h = 42 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Divide each side by '42'. h = 1 Simplifying h = 1
| -20=2m-7m | | 9i-3-15i=0 | | 8.4=5.7h+h+0.3h | | 132=6X+3(6X-12) | | 7*x-12=2 | | 5b(a)= | | 5X+7(1X-15)=27 | | -5-7(4-3x)=-82 | | 11g+g-3G=225 | | 3X+2(6X-14)=137 | | 9a^2-12a-1=0 | | -13z=-8 | | 12n-4n+4n=144 | | -13=6X+7(X-13) | | 6(6s+s)-24s=108 | | 112=4X+4(3X-4) | | 26.95=8.95+1.5r | | -2-4x-12=3x-3x | | 4y+x=180 | | -x(x^2-6x+5)=0 | | 4(5z+2z)-11z=68 | | 22=2X+3(2X-6) | | 912=612+25u | | .378+s=2.918 | | 120=5(3x+x)-12x | | 2n+3n+5n+8=40+8 | | 52=35+.5t | | 10x+12x-6x=48 | | (4x-5y)-(4x+7y)= | | 11+a-a=5+a | | g^2+20g+96= | | (-6+7i)-(-5-2i)= |